Determinant factors in the teaching-learning of sport from emotional perspective - Mauro Sánchez Sánchez; Juan Ángel Collado Martínez (Federación Extremeña de Balonmano; University of Extremadura, 2016)
From neuroscience and psychology it is highlighting the importance of emotions in learning (Diamond, 2012; Forés et al. 2015; Mora, 2013; Vázquez and Hervás, 2009). When the coach / teacher has emotional well-being and expresses positive attitudes are more effective learning. Also, goal-setting and regulation of emotions is crucial in the learning process. Therefore, the coach / teacher has the responsibility to make teaching approaches from an emotional perspective, where teaching when setting goals, positive learning climates and emotional regulation is considered.